Juridical Analysis in Overcoming Obstacles to the Development of Individual Companies in the Digital Era - Nurul Rahmawati; Parameshwara Parameshwara; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Batam Port is one of the strategic ports in Indonesia that plays an important role in the flow of goods and passengers and supports regional and international connectivity. As a port with mandatory pilotage waters, pilotage and towing services are vital components in ensuring the safety and efficiency of port operations. The imposition of Non-Tax State Revenue (PNBP) of 5% from these services aims to increase state revenue and the quality of port services. However, the implementation of this policy raises various challenges, such as overlapping levies that increase ship operational costs and low levels of user compliance.This study aims to analyze the legal regulations, implementation, and impact of the imposition and management of PNBP contributions of 5% from pilotage and towing services in Class II Pilotage Waters of Batam Port. The research method used is qualitative with data collection techniques through in-depth interviews, observations, and documentation studies. Research respondents included officials of the Batam Special Harbormaster and Port Authority Office (KSOP), Port Business Entities holding pilotage delegations, shipping companies, and port service user.The results of the study show that the imposition of 5% PNBP is supported by a strong legal basis, but its implementation still faces obstacles such as high operational costs due to overlapping levies and low understanding and compliance of service users. The management of PNBP funds that is not transparent is also an obstacle in achieving the goal of improving port services and infrastructure. To overcome this problem, efforts are needed to harmonize levy policies, increase transparency and accountability in fund management, and provide more effective education and socialization to the maritime community. Suggestions submitted include harmonization of policies between KSOP Batam and the Port Business Entity BP Batam, increasing socialization and education to service users, and reviewing regulations by the government to ensure port efficiency and competitiveness. With these steps, it is hoped that the implementation and management of 5% PNBP can be more efficient, fair, and provide optimal benefits for all stakeholders in Batam Port.